Pengaruh variasi ukuran serbuk dan persentase perekat terigu terhadap sifat fisik pellet kayu gelam - Andy Nugraha; Herry Irawansyah; Moh Noer Afifudin; Muhammad Muhammad; Rizqi Nor Al’Arisko (TURBO [Tulisan Riset Berbasis Online], 2022)
South Kalimantan is one of the natural habitats of gelam wood. In South Kalimantan, gelam wood can grow well and fertile. This makes the availability of gelam wood abundant and can be used for various purposes, one of which can be used as raw material for wood pellets (biomass energy). Wood pellets made from gelam wood have not been widely studied, so it is necessary to know the effect of the size of gelam wood powder and the addition of the percentage of adhesive on the physical properties of gelam wood pellets. Wood pellets made from gelam were made using various sizes of powder (mesh) 40, 50, and 60 as well as using flour adhesive (percentage of adhesive 5%, 10%, and 15%). Gelam wood pellets were then tested for physical properties in order to determine their performance. From the research that has been carried out, it is found that the volatile matter content, ash content, and water content tend to increase with the smaller size of the gelam sawdust. Meanwhile, the calorific value and fixed carbon content have a tendency to decrease with the smaller size of the gelam sawdust. volatile matter content, ash content, and water content tend to increase as the percentage of adhesive is increased. Meanwhile, the calorific value and fixed carbon content tend to decrease with the increase in the percentage of the amount of adhesive.